2022
DOI: 10.1002/slct.202201748
|View full text |Cite
|
Sign up to set email alerts
|

Lawesson's Reagent‐Mediated Deoxygenation Reactions

Abstract: In recent years, some new functions of Lawesson's reagent have been revealed, among which the deoxygenation reactions account for the most and have been applied in the syntheses of natural products and functional materials. However, this field has not been reviewed in detail. In continuation of our research interest in sulfur chemistry, herein we reviewed the recent advances in LR‐mediated deoxygenation reactions from the following four aspects: deoxygenation, dehydration, decarbonylation, and miscellaneous. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…9 In recent years, LR has been discovered as deoxygenation reagent and applied in the syntheses of natural products and functional materials. 10 In 2022, our research group developed a new method of LR-promoted deoxygenation of γ-hydroxylactams/succinimides or anhydrides for the syntheses of pyrroles or thiophenes through α,β-unsaturated lactam or thioester intermediates, and applied this method into the total syntheses of pyrrole-type Stemona alkaloids. 11 Therefore, we commenced our study by optimizing the reaction conditions based on our previously reported reaction conditions in LR-promoted deoxygenation of anhydrides.…”
mentioning
confidence: 99%
“…9 In recent years, LR has been discovered as deoxygenation reagent and applied in the syntheses of natural products and functional materials. 10 In 2022, our research group developed a new method of LR-promoted deoxygenation of γ-hydroxylactams/succinimides or anhydrides for the syntheses of pyrroles or thiophenes through α,β-unsaturated lactam or thioester intermediates, and applied this method into the total syntheses of pyrrole-type Stemona alkaloids. 11 Therefore, we commenced our study by optimizing the reaction conditions based on our previously reported reaction conditions in LR-promoted deoxygenation of anhydrides.…”
mentioning
confidence: 99%